A study on awareness regarding cigarettes and other tobacco products act (COTPA Act) among hospital staff of medical college, Kanpur: A mixed method study - Aradhana Yadav; Sonam; Samarjeet Kaur; Santosh K. Barman; Seema Barman (Journal of Family Medicine and Primary Care)
Context: In 2003, the government of India formulated “the cigarettes and other tobacco products Act (prohibition of advertisement and regulation of trade and commerce, production, supply, and distribution) (COTPA)”. The aim of the study is to evaluate hospital staff’s knowledge of the COTPA Act and their enablers and hurdles using qualitative analysis. Settings and Design: This study was conducted in GSVM Medical College, and this was a convergent parallel mixed-methods study, with a quantitative component (cross-sectional survey) complemented by a qualitative component (descriptive study). Methods and Material: A pre-tested, semi-structured, face-validated questionnaire was incorporated into the Epicollect5 application for data collection. The qualitative study was conducted among 11 hospital staff. Statistical Analysis Used: The collected data were imported into a Microsoft Excel spreadsheet and analysed with Jamovi version 2.0. To determine associations between variables, appropriate tests of significance were applied. For qualitative analysis, an interview guide was prepared. Results: On quantitative analysis, hospital personnel’s overall awareness of any tobacco control law was 59.4%, with 56.6% being tobacco abusers and 69.5% being non-abusers. On qualitative analysis by in-depth interview framework analysis, decalogues were taken from the responses provided by the participants. After that, the decalogues were divided into three keynotes which were openers, hurdles, and recommendations. Conclusions: Study demonstrates that more than half of the employees are already aware of COTPA Act but still need more coordinated effort from all responsible authorities of medical institute to increase COTPA Act awareness.